Job's body and the dramatized comedy of moralising - Southwood, Katherine (Routledge studies in the biblical world, 2021)
Introduction and methods -- Methinks the Job he doth Protest too Much -- The Tyranny of Tradition --Pride comes before a Fool: Job's loss of Social Status -- Is the answer for Job blowin' in the Wind?